2015
DOI: 10.5799/ahinjs.02.2015.03.0185
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of mycotic keratitis in north Maharashtra, India: A prospective study

Abstract: Objective: Corneal blindness is a major public health problem worldwide and mycotic keratitis is one of the predominant causes. Infection is difficult to treat and can lead to severe visual impairment or blindness. It is worldwide in distribution but is more common in tropics and subtropical region. Trauma is the major predisposing factor, followed by ocular or systemic defects, prior application of corticosteroids, and prolonged use of antibiotic eye drops. The purpose of this study was to document the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…Male: female ratio was 3:2. Similar results were found in a study done by Tukaram et al 7 where 24 cases (60%) were males and 16 (40%) were females. Our results also correlated with the study by Gopinathan et al 8 , who also reported that males (962) were affected more significantly (p < 0.0001) than females (390).…”
Section: Discussionsupporting
confidence: 91%
“…Male: female ratio was 3:2. Similar results were found in a study done by Tukaram et al 7 where 24 cases (60%) were males and 16 (40%) were females. Our results also correlated with the study by Gopinathan et al 8 , who also reported that males (962) were affected more significantly (p < 0.0001) than females (390).…”
Section: Discussionsupporting
confidence: 91%
“…These results are nearly similar to those reported by Gopinathan et al (2002) who found that the males were significantly more frequently affected than females (a ratio of 2.5:1). Also Kalshetti et al(2015) found that from 40 patients only 24(60%) were males and 16(40%) were females. 64% of patients were in the age group 20 to 50 years (Tilak etal.…”
Section: Discussionmentioning
confidence: 94%
“…Previous report recorded (42.9%) patients with fungal keratitis were farmers; one (14.3%) animal husbandman, one (14.3%) laborer, and 2 (28.6%) were housewives (Shokohiet al1999). Kalshetti et al (2015) reported that seven (50%) patients with fungal keratitis were farmers, three (21.4%) laborer and four (28.5%) were housewives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a prospective study on 40 patients with corneal ulcer was conducted over a 25 month period (October 2011 to November 2013) at a medical college in Dhule, northern Maharashtra [Kalshetti et al, 2015]. Microbiological tests on corneal scrapings from the patients confirmed a diagnosis of mycotic keratitis in 14; fungal growth in culture was obtained in 12 cases, while the other two were positive only by KOH preparation.…”
Section: Mycotic Keratitis In Maharashtramentioning
confidence: 99%